1982
DOI: 10.1002/j.1460-2075.1982.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of fibronectin, laminin-entactin, and entactin in Reichert's membrane by immunoelectron microscopy.

Abstract: Immunoelectron microscopy using protein A‐colloidal gold complexes of different sizes was used to study the relative distribution of extracellular matrix glycoproteins within Reichert's membrane (RM) of 13.5‐day mouse embryos. Labelling for fibronectin was distributed asymmetrically; the highest concentration occurring in the outermost layer adjacent to the trophoblast cells and negligible labelling in the inner matrix, beneath the parietal endoderm cells. Within the main body of the membrane, fibronectin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Extracellular matrix (ECM) proteins expressed by parietal endoderm to make Reichert's membrane were also abundant. Perlecan (heparin sulfate proteoglycan 2), type IV collagen (α1 and α2 chains only), laminin (α1, β1, and β2 chains), and nidogens 1 and 2 (Hogan et al, 1980;Semoff et al, 1982) were expressed in all XEN cell samples (see Table S2 in the supplementary material).…”
Section: Xen Cells Express Markers Of Extra-embryonic Endodermmentioning
confidence: 99%
“…Extracellular matrix (ECM) proteins expressed by parietal endoderm to make Reichert's membrane were also abundant. Perlecan (heparin sulfate proteoglycan 2), type IV collagen (α1 and α2 chains only), laminin (α1, β1, and β2 chains), and nidogens 1 and 2 (Hogan et al, 1980;Semoff et al, 1982) were expressed in all XEN cell samples (see Table S2 in the supplementary material).…”
Section: Xen Cells Express Markers Of Extra-embryonic Endodermmentioning
confidence: 99%
“…Within one passage of SOX7 overexpression (O/E), hESCs exhibit a flattened, epithilial morphology and express endoderm-associated proteins GATA-4, SOX17 and alpha fetoprotein (AFP) as well as pluripotency markers Oct4 and Nanog. Microarray-based expression profiling revealed that, respective to No Cre controls, SOX7 O/E hESCs upregulated ExE markers laminin subunit beta-1 (LAMB1), heparin sulfate proteoglycan (HSPG)2, and secreted protein acidic and rich in cystein (SPARC) (Hogan, Cooper et al 1980;Semoff, Hogan et al 1982;Mason, Taylor et al 1986). Additionally, SOX7 O/E hESCs exhibited a characteristic ExE gene expression profile which included GATA-4, GATA-6, HNF4A, FoxA2, To examine the effects of controlling ExE frequency independently of aggregate size on cardiac induction during hESC differentiation, forced aggregation of single cell suspensions in Aggrewells TM is a system that can be easily enabled to generate aggregates with varying ratios of SOX7 siRNA-transfected hESCs or SOX7 O/E hESCs.…”
Section: An Approach To Elucidate a Mechanism For The Effect Of Hesc mentioning
confidence: 99%
“…Collagenase type IV is a protease with high specificity for collagen, whereas dispase is a neutral metalloprotease that cleaves fibronectin and collagen type IV (Stenn et al, 1989). Because collagen type IV is a major component of Reichert's membrane (Hogan, 1980;Smith and Strickland, 1981;Hogan et al, 1984) and fibronectin is localized immediately adjacent to the trophoblast cells of the PYS (Semoff et al, 1982), we reasoned that a solution containing these enzymes would facilitate the removal of the PYS without affecting the egg cylinder-shaped conceptus. To determine whether a solution containing collagenase type IV and dispase facilitated removal of the PYS, we initially used a phosphate buffered saline (PBS) solution containing collagenase type IV and dispase at a concentration of 10 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…The parietal yolk sac is composed of trophoblast cells on the uterine side and parietal endoderm cells on the conceptus side. Between these two cellular layers lies Reichert's membrane, an acellular proteinaceous basement membrane composed mainly of type IV procollagen, laminin, entactin, and heparan sulfate proteoglycan (Hogan, 1980;Smith and Strickland, 1981;Semoff et al, 1982;Hogan et al, 1984). Removal of the parietal yolk sac is a prerequisite in the majority of experimental manipulations of egg cylinder conceptuses.…”
Section: Introductionmentioning
confidence: 99%